Structural and Cultural Aspects as the Potentials in the Development of Alternative Education for Fishermen Community - Prasetyo, Kuncoro Bayu (Universitas Negeri Semarang, 2019)
Fisherman community is a community that is generally vulnerable to poverty and underdeveloped education. However, this phenomenon is not found in the Banyutowo village fishermen community because they already have a view to improve their standard of living through education. However, the prioritized education is a formal education that has not been based on the values of local wisdom that they have so that educated people tend not to return to their villages. This study aims to determine the potentials of Banyutowo village that can support the development of alternative education based on local wisdom of the fishermen community. This study uses a qualitative approach with data collection methods namely observation, in-depth interview and FGD. Data validity uses source and method triangulation. The results show that: (1) The potentials of the Banyutowo village fishermen community in supporting the development of alternative education include structural and cultural aspects (2) Structural aspect is in the form of educational institutions managed by Christian and Muslim communities and local leadership figures who are able to make the villagers move forward (3) Cultural aspect is in the form of futuristic cultural values orientation, high motivation for achievement, and religious values that support them to become quality individuals.